Analyzing the Impact of Content Marketing, Instagram Social Media, and Customer Reviews on Repeat Purchases: A Case Study of PT Jokopi Indonesia Group - Oktaviani Dwi Wulansari; Rusdi Hidayat Nugroho (International Journal of Economics Development Research (IJEDR), 2024)
This study investigates the impact of content marketing, Instagram social media, and customer reviews on repeat purchases at PT Jokopi Indonesia Group, a coffee shop chain in Surabaya. Employing an associative research approach with a quantitative method, the study involved 200 Jokopi customers in Surabaya City with a purchase history of more than 2 times, selected through purposive sampling.The findings revealed that individually, content marketing, Instagram social media, and customer reviews significantly influence repeat customer purchases. Moreover, collectively, these three variables also exhibit a significant impact on repeat purchases. Hence, it can be inferred that content marketing strategies, Instagram social media presence, and customer reviews play a pivotal role in fostering customer loyalty and encouraging repeat purchases at Jokopi coffee shops.